Determinasi Niat Penggunaan Software Akuntansi pada UMKM: Pengujian Model UTAUT dengan Pendekatan PLS-SEM di Kota Padang - Julia Az-zahra; Willy Nofranita (Suria Academic Press, 2026)
This study aims to analyze the factors influencing the intention to use accounting software among Micro, Small, and Medium Enterprises (MSMEs) in Padang City by applying the Unified Theory of Acceptance and Use of Technology (UTAUT) model. This research employed a quantitative approach using purposive sampling, involving 100 MSME actors who have used accounting software. Data were collected through questionnaires and analyzed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method. The results indicate that the model has strong explanatory power, with an R-square value of 0.844. Empirically, performance expectancy and facilitating conditions have a positive and significant effect on behavioral intention, while effort expectancy and social influence do not have a significant effect. These findings suggest that perceived usefulness and the availability of supporting infrastructure are the main determinants of accounting software adoption among MSMEs. The study highlights the importance of improving digital literacy and strengthening technological infrastructure to support digital transformation in the MSME sector.